STUDI PENGOLAHAN AIR LIMBAH LABORATORIUM SECARA TERPADU (KOAGULASI, FILTRASI, ADSORPSI DAN PERTUKARAN ION) DENGAN SISTEM BATCH - Raimon, Raimon (Jurnal Dinamika Penelitian Industri, 2010)
Laboratory waste water is categorized as a toxic and hazardous waste. Research on laboratory waste water treatment which is resulted from COD analysis by applying coagulation, filration, adsorption and ion exchange in one step intergrated method has been done, in a laboratory scale of 1 liter volume of laboratory waste water. The purpose of this research is to get the optimum condition of treatment by variation the kind and concentration of coagulant, and the contact time in the adsorption process. Percentage decrease of pollutant has been observed through the measurement of some parameters such as: Total Dissolved Solid (TDS); Heavy metals such as iron (Fe), Manganese (Mn), and chromium (Cr), ammoniac and acidity (pH). The resultof this research that the best coagulant was 1 g/L Alum sulphate (AL2(SO4)3) and contact time was 2,5-5 minute. The result of analysis integrated laboratory waste water had been treated with batch system able to reduced total dissolved solution (TDS) 78,61 â 91,23%. Heavy metals Fe 97,61% - 99,99%, Mn 45,53% - 99,88%, Cr 92,54% - 99,98% and ammoniac 22,54% - 91,82%. Acidity (pH) of final laboratory waste water was 8,93.